Adaptive fuzzy multi‐surface sliding control of multiple‐input and multiple‐output autonomous flight systems. Issue 4 (1st February 2015) - Norton, Michael; Khoo, Suiyang; Kouzani, Abbas; Stojcevski, Alex
Abstract : In this study, we proposed an adaptive fuzzy multi‐surface sliding control (AFMSSC) for trajectory tracking of 6 degrees of freedom inertia coupled aerial vehicles with multiple inputs and multiple outputs (MIMO). It is shown that an adaptive fuzzy logic‐based function approximator can be used to estimate the system uncertainties and an iterative multi‐surface sliding control design can be carried out to control flight. Using AFMSSC on MIMO autonomous flight systems creates confluent control that can account for both matched and mismatched uncertainties, system disturbances and excitation in internal dynamics. It is proved that the AFMSSC system guarantees asymptotic output tracking and ultimate uniform boundedness of the tracking error. Simulation results are presented to validate the analysis.